Associations of Proanthocyanidin Intake with Renal Function and Clinical Outcomes in Elderly Women - Ivey, Kerry L. (Public Library of Science, 2013)
BACKGROUND: Progression to chronic renal failure involves accelerated atherosclerosis and vascular calcification. Oxidative stress and endothelial dysfunction play a role in renal failure pathophysiology. In addition to improving vascular health and function, proanthocyanidins have been shown to exert renoprotective effects in animal models. Thus we hypothesize that proanthocyanidins may contribute to the maintenance of healthy renal function. OBJECTIVE: Determine the association of habitual proanthocyanidin intake with renal function and the risk of clinical renal outcomes in a population of elderly women. DESIGN: 948 women aged over 75 y, free of prevalent renal disease at baseline, were randomly selected from ambulant Caucasian women. Proanthocyanidin consumption was determined using a validated food frequency questionnaire and the United States Department of Agriculture proanthocyanidin food content database. Fasting serum cystatin C and creatinine were assessed at baseline. Renal failure hospitalisations and deaths were assessed over 5 years of follow-up through the Western Australia Data Linkage System. RESULTS: Compared to participants with low consumption, participants in the highest tertile of proanthocyanidin intake had a 9% lower cystatin C concentration (P<0.001). High proanthocyanidin consumers were at 50% lower risk of moderate chronic kidney insufficiency, and 65% lower risk of experiencing a 5-year renal disease event (P<0.05). These relationships remained significant following adjustment for renal disease risk factors and diet-related potential confounders. CONCLUSION: Increased consumption of proanthocyanidins was associated with better renal function and substantially reduced renal associated events, which has been supported by mechanistic and animal model data. Proanthocyanidin intake should be further examined as a dietary contributor to better renal health.